Constructing virtual 5-dimensional tori out of lower-dimensional network cards - Andújar, Francisco J.; Fröning, Holger (Concurrency and computation, 2019)
In the Top500 and Graph500 lists of the last years, some of the most powerful systems implement a torus topology to interconnect the millions of computing nodes they include. Some of these torus networks are of five or six dimensions, which implies an additional difficulty as the node degree increases. In previous works, we proposed and evaluated the nD Twin (nDT) torus topology to virtually increase the dimensions a torus is able to implement. We showed that this new topology reduces the distances between nodes, increasing, therefore, global network performance. In this work, we present how to build a 5DT torus network using a specific commercial 6-port network card (EXTOLL card) to interconnect those nodes. We show, using the same number of cards, that the performance of the 5DT torus network we are able to implement using our proposal is higher than the performance of the 3D torus network for the same number of compute nodes.